Integrating English Language Teaching (ELT) Into Islamic Boarding Schools: A Review of Strategy and Challenges - Fitria, Tira Nur (Universitas Kapuas, 2023)
This research describes English Language Teaching (ELT) strategies and challenges in Islamic Boarding Schools. This research is library research. The analysis shows that teaching English needs a system or method during the implementation. Besides, teaching foreign languages, such as English, faces challenges/difficulties/problems during the implementation. Factors such as teacher education background, enthusiasm level, comprehension of the student's character, and norms applied at Islamic Boarding Schools determine which strategies English teachers implement. Even though teachers attempt to develop their teaching strategies innovatively, stagnant techniques are used to meet students' requirements. By understanding a student's character, teachers can select the most effective method for teaching English. Modern Islamic boarding schools combine traditional and modern systems to prepare students for the challenges of the times. English is used to explore and implement the richness and beauty of Islamic boarding schools' knowledge of knowledge objects and conditions related to this era. English Language Instruction is essential for Pesantren, and it must be well-planned and organized to achieve high-quality English teaching and learning. Foreign languages must be used as the language of everyday life in Islamic boarding schools. The most important details are the teacher's dedication, the students' awareness of learning English, the challenges teachers face in providing modern learning, and the lack of exposure to Arabic. Arabic and English are the priority languages to be taught, as they are essential for understanding the Qur'an, hadiths, and globalization.